Adaptation of Climate Change to Vulnerability of Raw Water Availability in Bantaeng, South Sulawesi. Issue 1 (May 2021) - Rusli, M; Chaerul, M; Marzuki, I
Abstract: Various processes triggering global climate change and climate change have been accepted by many parties as a necessity characterized by global warming, with a direct impact on the hydrological cycle, so that climate change is believed to have a real impact on water resources. Taking into account the possible consequences of climate change, it will be extremely important to examine how fluctuation in temperature and rainfall pattern shift will affect the water supply system. With this climate change, it will lead to vulnerability to the availability of raw water. The vulnerability referred to in Bantaeng was simply determined by three factors that were considered dominant, namely water needs, water sources, and community welfare. The analysis results showed that there was a higher risk increase which was influenced by hydrogeological conditions related to groundwater potential. Optimal groundwater management was expected to contribute as an adaptation effort to climate change risks to water sources.